MENINGKATKAN HASIL BELAJAR SOSIOLOGI PADA MATERI PERUBAHAN SOSIAL MELALUI PEMBELAJARAN INKUIRI SOSIAL SISWA KELAS XII IPS 2 SMA NEGERI 1 MERANGIN - Marya Setiawati, S.Sos (LP3M | STKIP YPM Bangko, 2022)
This study aims to improve the learning outcomes of sociology by trying a social inquiry learning model. The research method used is classroom action research. The data were analyzed using quantitative analysis, which emphasized on improving student learning outcomes in depth. Next, analyze the problems that arise and then reflect on to find alternative solutions. The subjects of this study were students of class XII IPS 2 SMA Negeri 1 Merangin, totaling 30 people. The results showed that: (1) Sociology learning outcomes while using the social inquiry learning model could increase, it was seen in the first cycle that the average value of the pretest was 63.28 and the posttest was 71.82. This shows an increase in the class average score of 8.54. In the second cycle, it can be seen that there is an increase in student learning outcomes, the average score of the pretest is 63.79 and the posttest is 74.41. This shows an increase in the class average score of 10.62. (2) The responses of students in class XII IPS 2 at SMA Negeri 1 Merangin to the use of the social inquiry learning model indicate that students enjoy learning Sociology with this learning model.